E-services Adoption model and the influential factors in a developing Nation - BARBOUR EL RASSI, Mary Ann (Proche-Orient Études en management, 2019)
The fast development and expansion of the internet have impacted enormously the service industry structures globally. E-service symbolizes the digitalization of all processes and value chains in the service industry and surfaces as a term describing the ICTs applications on services and the insinuations for the value chain. While many studies had focused on identifying factors that help organizations to ensure success and avoid failure, investigating the e-business adoption process in a dynamic approach and that is by explaining how external and internal factors are enacted in different ways have been widely neglected in Developing Countries. Our research aims at addressing this gap in knowledge by proposing a multilevel dynamic reading of a theoretical model that was previously developed in a Developing Country context (PERM model). Considering that the use of these scales in a different cultural context requires an adaptation and a validation test (Jolibert and Jourdan, 2006), it was important to measure the quality of the selected scales in our research specific context. We did it in two steps: 1. The purification of the scale through a principal component analysis (PCA), 2. The examination of the reliability of each latent variable by the mean of Cronbach’s alpha. The results of this research contribute to the understanding of this new phenomenon and propose an adjusted model to be tested in the future on a larger sample.